Motor control assessment of community-dwelling older adults with depressive symptoms - Lucas Eduardo Antunes Bicalho; Maicon Rodrigues Albuquerque; Jonas Jardim de Paula; Guilherme Menezes Lage (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMSThe purpose of this study was to investigate how depressive symptoms mediate different motor control requirements in elderlies and to assess the concurring effects fomented by the interaction between aging and depressive symptoms, providing indirect measures of brain functionality. METHODS Sixty-eight elderlies were paired in terms of age and gender and were equally distributed into depressed and nondepressed groups, according to their score on the Beck Depression Questionnaire. The participants performed the Grooved Pegboard Test placing and withdrawing pegs while execution time and error rate were measured. RESULTS This investigation revealed that depressive symptoms exert a broad effect upon motor control, although that the symptom intensity, as well as the interaction between aging and depression intensity, were exclusively correlated with withdrawal task, suggesting that there is a greater effect upon motor acts with higher frontal lobe requirements. CONCLUSION The discrimination of motor control aspects provides a valuable contribution for the understanding of the underlying neurophysiology of the interaction between aging and depression as it represents an indirect measure of cerebral dysfunction. Further, these findings may still have clinical implications, as they can promote more rational approaches to the elaboration of preventive measures that help maintain the functional capability of depressed elderlies.